Ruangrupa Community as an Alternative Urban Cultural Social Space - Hidayat, Rakhmat; Setiyaji, Ibnu; Afdhal (Indonesian Journal of Sociology, Education, and Development, 2023)
Urban environments, as complex settings, face competition for space due to various spatial practices. Certain powers and influences within urban spaces contribute to the shrinking of public spaces that accessed by the community. The purpose of this article is to explore the community’s efforts to fight for social space within the context of Lefebvre’s understanding of the city as the product of abstract capitalism. Qualitative research method with phenomenology study as a method is used in this research. This study answers on how aware the community is of the importance of space in urban life. “Ruangrupa” builds social space through art practices involving the community as an alternative to respond to the dominance of commercial space in the city. Through discourses on the city, culture, and education, “Ruangrupa” builds an antithesis to commercial space and encourages the community to engage in daily activities in urban space as a novelty in this research.